Psikhologicheskaya teoriya sportivnoi deyatel'nosti: aktual'nye napravleniya razvitiya - Gorskaya, G. B. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The article is dedicated to the prerequisites of a sporting activities special theory conceptual bases. The productive basis of psychological prerequisites to the athletes professional self-realization can serve the conception of an active personality. The main characteristics of that conception are the next: - the active action principles of the athlete's personality resources' self-realization; - the considering of an active personality in the real vital context of the sporting activities.